2015
DOI: 10.1155/2015/203136
|View full text |Cite
|
Sign up to set email alerts
|

The Difference between Growth Factor Expression after Single and Multiple Fractures: Preliminary Results in Human Fracture Healing

Abstract: Objectives. Circulating levels of VEGF-A (Vascular Endothelia Growth Factor-A), TGF-β1 (Transforming Growth Factor-beta 1), and M-CSF (Macrophage-Colony Stimulating Factor) were found to be predictors of bone healing and therefore prognostic criteria of delayed bone healing or nonunion. The aim of this study was to evaluate a potential rise of these markers in patients with multiple fractures of long bones compared to patients with single fractured long bone. Methods. 92 patients were included in the study and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…In conclusion it is known that local and systemic concentrations of different osteogenic cytokines increase during physiological fracture healing, in particular sufficient serum concentrations of TGF-ß have been shown to be pivotal to fracture healing [ 36 ]. It has been reported that TGF-ß and BMPs are capable of inducing each others expressions [ 33 , 34 ], however patients with failed bone healing are known to have impaired local BMP concentration, furthermore the current study showed that the concentration of TGF-ß in concerned patients is decreased during the initial 12 months; indicating that BMP-7 and TGF-ß have to be present in fracture healing in a sufficient concentration [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…In conclusion it is known that local and systemic concentrations of different osteogenic cytokines increase during physiological fracture healing, in particular sufficient serum concentrations of TGF-ß have been shown to be pivotal to fracture healing [ 36 ]. It has been reported that TGF-ß and BMPs are capable of inducing each others expressions [ 33 , 34 ], however patients with failed bone healing are known to have impaired local BMP concentration, furthermore the current study showed that the concentration of TGF-ß in concerned patients is decreased during the initial 12 months; indicating that BMP-7 and TGF-ß have to be present in fracture healing in a sufficient concentration [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Following a fracture, a crosslinked fibrin meshwork is formed by a platelet clump and initiation of the clotting cascade, with generation of thrombin stimulating the cleavage of fibrinogen to fibrin. Consequently, a cohort of cytokines and growth factors, such as vascular endothelial growth factor (VEGF), transforming growth factor‐ β 1 (TGF β 1) and bone morphogenetic protein (BMPs), are released from platelet degranulation and the periosteum, and are trapped by the developing haematoma (Binder et al ., ; Borges et al ., ). Besides releasing osteogenic factors, the periosteum has also been shown to have a vital role in the maturation of fracture haematomas by mediating chondrogenesis and endochondral ossification (Ozaki et al ., ).…”
Section: Influence Of Haematoma On Growth Factorsmentioning
confidence: 99%
“…The systemic and local response in patients with impaired fracture healing have been examined in a few studies using blood samples or specimens of bone tissue, respectively. [11][12][13] However, in order to fully understand the healing process to bone damage, the local molecular and morphological response is optimally examined in discriminative animal models. Both the local histology and gene expression after bone damage are well characterized in rodents.…”
Section: Introductionmentioning
confidence: 99%